EFEKTIVITAS IMPLEMENTASI TRAFFICKING VICTIMS PROTECTION ACT OF 2000 (TVPA) OLEH AMERIKA SERIKAT DALAM MENANGANI PERDAGANGAN MANUSIA GLOBAL TAHUN 2000–2016 - Pangestika, Okta Rahasti (Global and Policy Journal of International Relations, 2017)
ABSTRACTHuman trafficking is one of the dark side of globalisation. The vast growing of world integration become a fertilizer for human trafficking world wide. At the end of the rope, US responses with the law enforcement againts modern-day slavery through establishment of Trafficking Victims Protection Act of 2000 (TVPA). Above all the reasons, law enforcement factor manifested in the law effectivity theory is the main tool analysis for this paper. Despite the law factor, US national interest also played a deterministic aspect to analyze TVPA effectivity world wide. This papers argues on those side in order to explain effectivity of US anti-trafficking law againts world wide human trafficking within 2000-2016.Keywords: Modern-day slavery, Trafficking Victims Protection Act of 2000 (TVPA), effectivity, human traffickingDOI: https://doi.org/10.33005/jgp.v5i02.1890